A Genome-Wide Scan of DNA Methylation Markers for Distinguishing Monozygotic Twins. (26th October 2015) - Du, Qingqing; Zhu, Guijun; Fu, Guangping; Zhang, Xiaojing; Fu, Lihong; Li, Shujin; Cong, Bin
Abstract : Identification of individuals within pairs of monozygotic (MZ) twins remains unresolved using common forensic DNA typing technology. For some criminal cases involving MZ twins as suspects, the twins had to be released due to inability to identify which of the pair was the perpetrator. In this study, we performed a genome-wide scan on whole blood-derived DNA from four pairs of healthy phenotypically concordant MZ twins using the methylated DNA immunoprecipitation sequencing technology to identify candidate DNA methylation markers with capacity to distinguish MZ twins within a pair. We identified 38 differential methylation regions showing within-pair methylation differences in all four MZ pairs. These are all located in CpG islands, 17 of which are promoter-associated, 17 are intergenic islands, and four are intragenic islands. Genes associated with these markers are related with cell proliferation, differentiation, and growth and development, including zinc finger proteins, PRRX2, RBBP9, or are involved in G-protein signaling, such as the regulator of G-protein signaling 16 . Further validation studies on additional MZ twins are now required to evaluate the broader utility of these 38 markers for forensic use.